Climacus' Miracle: Another Look at "the Wonder" in Philosophical Fragments through a Spinozist Lens - Marcar, G.P. (Kierkegaard studies / Yearbook, 2019)
In Chapter 2 of the Philosophical Fragments, Søren Kierkegaard's pseudonym Johannes Climacus poetises about a "king who loved a maiden." Climacus concludes this venture with a bold claim: what he has just described is "so different from any human poem" that it should not be regarded as a poem at all, but as "the wonder" [Vidunderet] which leads one to exclaim in adoration that "[t]his thought did not arise in my own heart!" In the subsequent chapter of Philosophical Fragments, Climacus proceeds to offer a number of arguments against demonstrations of God's existence, leading many scholars to conclude that he represents an unequivocally anti-rationalist perspective. Against such interpretations, this paper will seek to highlight how Climacus' claims track those of the seventeenth century Dutch lens-grinder and rationalist philosopher, Baruch Spinoza. From this, it will be argued that "the wonder" in Climacus' thought takes the form of an indirect, ethico-existentialist argument for the truth of Christianity's incarnate God.